Development of Redox Animation Application to Enhance Students Critical Thinking Skills on Oxidation Reduction Reaction Topics - Bimanyu, Anjas; Sukarmin, Sukarmin (Jurnal Pijar Mipa, 2024)
Critical thinking skills are one of the four 21st-century skills defined as the ability to reason rationally and logically. In the context of chemistry, critical thinking plays a vital role as it is required to understand chemical concepts, mechanisms, equations, reactions, and elements, as well as the ability to make appropriate judgments. However, based on previous research and field surveys, it was found that students' critical thinking skills are generally low. Three levels of chemical representation in chemistry need to be connected integrally to develop an understanding of chemical concepts and critical thinking. Integrating the three levels of representation can be done through visualisation media in animation. Thus, a visual communication media that includes three representative levels is developed to improve critical thinking skills and facilitate students' understanding of chemical materials, especially in the context of reduction and oxidation reactions, namely the Redox Animation application. In this article, this research aims to develop a Redox Animation application that is feasible in terms of two learning media feasibility criteria, namely validity and practicality. The development research model used in this research is the Sukmadinata model, which has three main stages: preliminary studies, model development, and model testing. This study is limited to the trial step. The research data shows that the Redox Animation application developed meets the feasibility in development research on validity criteria with the acquisition of a content validity mode score of 4 with valid criteria and a construct validity mode score of 4 with valid criteria and practicality criteria with the acquisition of a percentage in a learner response questionnaire of 96.33% with efficient criteria. Thus, the Redox Animation application is declared feasible for enhancing students' critical thinking skills on redox reaction topics based on validity criteria and practicality criteria in development research.